Adoption of Rice Production Technologies by Tribal Farmers of Mandla District of M.P. - Singh, P K; Barman, K K (Indian Journal of Extension Education, 2011)
Adoption of improved technologies are very important aspects in extention process. Large number of technologies evolved in the field of agriculture is not being accepted and adopted at its fullest extent by the farmers. The gap between recommendations made by the scientists and actual use by farmers is frequently encountered. The study was conducted in a tribal district Mandla of Madhya Pradesh. Four blocks, namely, Gughari, Bichiya, Narayan Ganj and Niwas were selected purposively. Results shows that the tribal farmers might have been convinced with the merits of using HYVs and nitrogen fertilizers which helped in building favourable attitude towards adoption of these technologies. Farmers are convinced about importance of pest and weed management, but they are not adopting the improved technologies due to several constraints. The extent of adoption of majority of the practices like adoption of P, K, Zn fertilizers and plant protection is either partial or nil due to lack of knowledge and awareness.